PRIORITAS STRATEGI PEMBANGUNAN HUTAN KOTA PEKANBARU BERDASARKAN PARTISIPASI PARA PIHAK DENGAN METODE AHP - Amrad Rabbani Piliang; M. Mardhiansyah; Tuti Arlita (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The strategy already worked in management Forest City Pekanbaru not yet give the maximal result. It can be showed from less developing of the potency in forest city. The strategy should be support coherent management and give the best the result, other ways the strategy can not defined the actor in order to building with effective. The aim of this research to determined the main strategy management of this forest city based on the participation of the all side. The method in this  research use AHP method (Analytical Hierarchy Process). The result of this research showed that the criteria to determined the strategy to building Forest City Pekanbaru based on the partisipation of the people according the goverment is social importance (0,377), society is ecology importance (0,442)and the businessman is social importance (0,377). According all the participation of people finded the priority strategy building city is (1) increase the function of forest city (0,353), (2) sociliaze from government (0,242), (3) facility (0,238) and (4) controlling the activity of society (0,167). Keywords: AHP, The Priority of Building Strategy, Forest City Pekanbaru.